Amplification and Direct Sequence Analysis of the 23S rRNA Gene from Thermophilic Bacteria. (February 2001) - Ibrahim, Ashraf; Hofman-Bang, Jacob; Ahring, Birgitte K.
We present a simplified and fast method to obtain high-quality sequences directly from PCRs without the traditional gel purification. We also report on an improved method to obtain sequence-quality PCR products from microorganisms that are difficult to lyse with no need for DNA extraction. The technique uses exonuclease I and shrimp alkaline phosphatase to degrade residual dNTPs and primers. Our technique is shown to work on both Gram-positive and Gram-negative bacteria.